FAO fisheries report N.540 - FAO (FAO, 1996)
The document was to review the institutional credit arrangements for fish marketing and utilizations as well as to discuss on-going credit programmes for the fisheries sector in the light of fisheries management measures and regulations which are presently being introduced in most countries of the region. The document looked at the current and future investment and credit needs for fish marketing and processing and in relation to community-based fisheries management.